2010
DOI: 10.1007/s11104-010-0357-7
|View full text |Cite
|
Sign up to set email alerts
|

Is vegetation composition or soil chemistry the best predictor of the soil microbial community?

Abstract: With the species composition and/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 50 publications
4
83
1
Order By: Relevance
“…We used this novel approach to characterize plant composition among plots and found that the plant community was a stronger predictor of the fungal community than were soil properties or geographic distance. These results are consistent with those of Mitchell et al (2010), who showed that plant community composition was a better predictor of microbial community composition than was soil chemistry across a plant successional gradient in a boreal ecosystem. Our findings support those of Peay et al (2013), who found a significant correlation between plant community composition and fungal community composition in three tropical forests, and further show that fungal community composition is more closely linked to plant community composition than to either environmental variability or geographic distance.…”
supporting
confidence: 91%
“…We used this novel approach to characterize plant composition among plots and found that the plant community was a stronger predictor of the fungal community than were soil properties or geographic distance. These results are consistent with those of Mitchell et al (2010), who showed that plant community composition was a better predictor of microbial community composition than was soil chemistry across a plant successional gradient in a boreal ecosystem. Our findings support those of Peay et al (2013), who found a significant correlation between plant community composition and fungal community composition in three tropical forests, and further show that fungal community composition is more closely linked to plant community composition than to either environmental variability or geographic distance.…”
supporting
confidence: 91%
“…Many studies have found plant species composition to be a good indicator of belowground community composition (Mitchell et al 2010;Thoms et al, 2010). In these studies the differences between plants of the same species cannot be distinguished, replicates of samples were combined for microbiological analysis, so differences found represent the general influence of tree species in a large area.…”
Section: Discussionmentioning
confidence: 99%
“…Reynolds et al 2003;van der Heijden et al 2008). Mitchell et al (2010b) studied the relationship between the SMC, soil chemical properties and plant composition along a successional gradient from open moorland to Betula woodland. They showed that the vegetation community is as good a predictor of the SMC as the soil chemistry.…”
mentioning
confidence: 99%